Oral Phosphatidylcholine Improves Intestinal Barrier Function in Drug-Induced Liver Injury in Rats - Meijuan Chen; Haijun Huang; Pengcheng Zhou; Jiajie Zhang; Yining Dai; Danhong Yang; Xuegong Fan; Hongying Pan (Gastroenterology Research and Practice)
Objective. Phosphatidylcholine (PC) is the major surface-active phospholipid and creates a hydrophobic nature to the surface. It has been reported to reverse the progression of liver fibrosis and to improve liver function. The aim of the present study was to evaluate the effects of orally administered PC on intestinal barrier function (IBF) in rats with drug-induced liver injury. Method. Rats with carbon tetrachloride- (CCl4-) induced liver injury were treated with 100 mg/kg PC once daily for 21 days. The effects of PC therapy on (i) liver function and portal pressure, (ii) intestinal and hepatic histology, and (iii) plasma endotoxin, diamine oxidase (DAO), and tumour necrosis factor- (TNF-) α levels were investigated. Results. PC therapy reduced portal pressure and improved the liver function in CCl4-induced liver injury. In PC-treated liver injury rats, collagen fibres were gradually decreased, while the disordered arrangement of hepatocytes and disorganized hepatic lobules were partially repaired, and inflammatory cell infiltration was decreased in the fibrous tissue. Lower inflammatory cell infiltration in the ileum improved intestinal histology, and reduced serum DAO levels were observed in PC-treated cirrhotic rats. These changes were associated with reduced inflammatory activity, as indicated by decreased serum TNF-α levels and plasma endotoxin levels. Conclusions. These results suggest that PC therapy is hepatoprotective and is able to restore IBF and reduce endotoxaemia in rats with drug-induced liver injury.